COMPARISON OF THE EFFECTIVENESS OF BOARD GAME AND SONG FOR THE CHILDREN’S SPEAKING SKILL - Rabiatul Adawiyah (Jurnal Penyelidikan Sains Sosial, 2021)
This study aims to determine the effectiveness of the board game and song inimproving speaking skills in kindergarten children. A total of 40 kindergarten children aged 5-6 years in a school in Sumbawa, West Nusa Tenggara Indonesia, with details of 20 children forgroup A and 20 children for group B who were involved in this study. This research is anexperimental study with a static group pretest posttest design. The research data were obtainedthrough the t-test to obtain the min scores of the subjects from the two research groups. Theresults were analyzed using SPSS 22 for windows. The results showed that the final scoreobtained by group A was 59.60 while the final score for group B was 60.20. In conclusion, thereis a significant difference as a whole based on the final score of the two groups of 0.6. Thisshows that both board game and song learning media have an influence on children's speakingability, but the song method has a more effective effect in improving children's speaking abilitycompared to board games.